Are changes in synovial fluid volume or distribution a determinant of biomechanical effects of passive joint movements?. (1st October 2016) - van Trijffel, Emiel; de Maeseneer, Michel; Buzzatti, Luca; Oostendorp, Rob A.B.; Scafoglieri, Aldo; Cattrysse, Erik
Abstract : Objectives : Biomechanical mechanisms underlying passive joint techniques commonly used in musculoskeletal medicine such as mobilization and manipulation are largely unknown. We aimed to visualize and measure in vivo time-dependent changes in the volume or distribution of synovial fluid after passive joint movements. Methods : Experiments were conducted in three healthy subjects using magnetic resonance imaging (MRI) and ultrasonography (US) for visualizing and measuring synovial fluid volume and distribution in joints of the upper cervical spine, the knee joints, and the metacarpophalangeal joints of the second and third fingers up to 60 minutes before and after passive motion assessment, mobilization, and/or high-velocity, low-amplitude thrust manipulation. Results : MRI could not detect any fluid in the articular space of the lateral atlanto-axial joints. Using US, the antero-posterior diameter of the suprapatellar recess was decreased from 11.0 to 9.0 millimetres in one subject 30 minutes after mobilization of the knee. US imaging of the palmar recesses of the metacarpophalangeal joints was found insufficiently reproducible. Conclusions : In our experiments, current techniques for MRI and US were not appropriate for visualization and measurement of in vivo time-dependent changes, if any, in the volume or distribution of synovial fluid after passive joint movements. As a limitation, we did not estimate any measurement error of US. New, innovative research is needed to generate evidence on the biomechanical effects of passive joint techniques commonly used in musculoskeletal medicine.